HUBUNGAN KECERDASAN INTERPERSONAL DENGAN MINAT BELAJAR SISWA KELAS IV SDN GUGUS 3 KOPANG - Ahmad Tohirudin; Darmiany Darmiany; Husniati Husniati; I Ketut Widiada (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2022)
This study aims to describe the relationship between interpersonal intelligence and learning interest in fourth grade students of SDN Gugus 3 Kopang in the 2019/2020 academic year. This research is a quantitative descriptive type of correlational research. The population of this study were all students of class IV SDN Cluster 3 Kopang totaling 182 students. The sampling technique used was simple random sampling with a sample of 125 students. The data collection technique in this research is a questionnaire. The data were analyzed with the help of SPSS version 16. The research hypothesis testing was analyzed using product moment correlation calculations to determine the relationship between interpersonal intelligence and student interest in learning. The results showed that there was a significant relationship between interpersonal intelligence and student interest in learning as indicated by rcount of 0.704 while rtable with N = 125 at the 5% significance level was 0.176, so rcount > rtable (0.704 > 0.176). The contribution (contribution) of interpersonal intelligence variable to interest in learning is 49.5% in the medium category.